Association between social capital and self-perception of health in Brazilian adults - Mathias Roberto Loch; Regina Kazue Tanno de Souza; Arthur Eumann Mesas; Alberto Durán González; Fernando Rodriguez-Artalejo (Universidade de São Paulo, 2015)
OBJECTIVE To investigate the association between social capital and social capital and self-perception of health based on examining the influence of health-related behaviors as possible mediators of this relationship. METHODS A cross-sectional study was used with 1,081 subjects, which is representative of the population of individuals aged 40 years or more in a medium-sized city in Southern Brazil. The subjects who perceived their health as fine, bad or very bad were considered to have a negative self-perception of their health. The social capital indicators were: number of friends, people from whom they could borrow money from when needed; the extent of trust in community members; whether or not members of the community helped each other; community safety; and extent of participation in community activities. The behaviors were: physical activity during leisure time, fruits and vegetable consumption, tobacco use and alcohol abuse. The odds ratios (OR) and confidence intervals (CI) 95% were calculated by binary logistic regression. The significance of mediation was verified using the Sobel test. RESULTS Following adjustment for demographic and clinical variables, subjects with fewer friends (OR = 1.39, 95%CI 1.08;1.80), those who perceived less frequently help from people in the neighborhood (OR = 1.30, 95%CI 1.01;1.68), who saw the violent neighborhood (OR = 1.33, 95%CI 1.01;1.74) and who had not participated in any community activity (OR = 1.39, 95%CI 1.07;1.80) had more negative self-perception of their health. Physical activity during leisure time was a significant mediator in the relationship between all social capital indicators (except for the borrowed money variable) and self-perceived health. Fruit and vegetable consumption was a significant mediator of the relationship between the extent of participation in community activities and self-perceived health. Tobacco use and alcohol abuse did not seem to have a mediating role in any relationship. CONCLUSIONS Lifestyle seems to only partially explain the relationship between social capital and self-perceived health. Among the investigated behaviors, physical activity during leisure time is what seems to have the most important role as a mediator of this relationship.